2015
DOI: 10.17306/j.afs.2015.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of insect gall extracts of Pistacia integerrima

Abstract: Background. Pistacia integerrima (P. integerrina) insect galls are widely used in ayurveda and siddha system of medicine as karkatasringi. The use of leaf galls as a rejuvenator may be attributed to antioxidant property, however there is less scientifi c evidence. Therefore, the aim of this study was to evaluate the chemical composition and the antioxidant potential of leaf gall extracts (aqueous and ethanol) of P. integerrina, which is extensively used in the preparation of traditional medications. Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…However, ROS elevation upon PI treatment was absent in A549 cells suggesting a different mechanism of action associated with PI that mediates apoptosis in A549 cells ( Figures 3D,E ). We did not observe an increase in ROS probably due to the anti-oxidant properties of Pistacia integerrima , as previously reported ( Eshwarappa et al, 2015 ). To gain insights into the components of cellular machinery that trigger apoptosis upon PI treatment, we investigated other programmed cell death forms that involve autophagy.…”
Section: Discussionsupporting
confidence: 88%
“…However, ROS elevation upon PI treatment was absent in A549 cells suggesting a different mechanism of action associated with PI that mediates apoptosis in A549 cells ( Figures 3D,E ). We did not observe an increase in ROS probably due to the anti-oxidant properties of Pistacia integerrima , as previously reported ( Eshwarappa et al, 2015 ). To gain insights into the components of cellular machinery that trigger apoptosis upon PI treatment, we investigated other programmed cell death forms that involve autophagy.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the TPC and/or TFC were closely associated with antioxidant activities. Phenolics and flavonoids may be the main antioxidant compounds [30]. This finding is consistent with the chemical constituent in each extract and the antioxidant activities of individuals.…”
Section: Multivariate Analysis (Pca)supporting
confidence: 84%
“…[ 12 ] Although the accepted source of Karkatasringi is the galls of Rhus succedanea L. , however Pistacia integerrima and T. chebula are also generally used in the preparations. [ 9 13 ] Gall extracts of T. chebula have been found to possess antioxidant, antiinflammatory, antibacterial, antityrosinase, and antiaging activities. [ 14 15 16 17 18 19 ] In an earlier study it was found that the ethanolic leaf gall extract T. chebula possessed potent anthelmintic activities.…”
Section: Introductionmentioning
confidence: 99%